Lightning talk: Supporting software sustainability with lightweight specifications - Contrastin, M; Danish, M; Orchard, D; Rice, A (CEUR Workshop Proceedings, 2016)
Lightweight specifications support software maintainability by providing a way to verify that any changes to a code base preserve certain program properties. We give two examples of lightweight specifications for numerical code: $\textit{units-of-measure types}$ which specify the physical units of numerical quantities in a program; and $\textit{stencil specifications}$ which describe the pattern of data access used in array computations. Not only can we automatically verify that a program correctly implements these requirements but specifications provide documentation for future developers. Specifications can also be inferred and generated automatically in some cases, further reducing programmer effort. We finish by identifying future potential specification techniques to ease the maintenance and comprehension of scientific code.